Contemporary Challenges of Transport Systems and Traffic Engineering 13th Scientific and Technical Conference "Transport Systems. Theory and Practice 2016" Katowice, Poland, September 19-21, 2016 Selected Papers - Macioszek, Elżbieta; Sierpiński, Grzegorz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The publication contains numerous valuable guidelines one will find particularly useful while making decisions concerning development and improvement of transport systems. It provides a multitude of case studies connected with diverse problems of both technical and organisational nature. The knowledge displayed while discussing practical examples as well as the decision making support systems described in the publication will certainly attract interest of those who face the challenge of seeking solutions to problems of contemporary transport systems on a daily basis. Consequently, this publication is dedicated to local authorities involved in planning and preparation of development strategies for specific transport related areas (in both urban and regional dimension) as well as to representatives of business and industry, being those who participate directly in the implementation of traffic engineering solutions. The guidelines provided in individual chapters of the publication willmake it possible to address the given problem in a technologically advanced manner and simplify the choice of appropriate strategies (including those related to increasing competitiveness of public transport, integration of supply chains or route planning support by means of technologically advanced systems and applications). On the other hand, since the publication also concerns the new approach to theoretical models (including travel models, capacity models, road condition modelling and speed-volume relationship), it will raise interest among researches and scientists studying this body of problems. The publication entitled Contemporary Challenges of Transport Systems and Traffic Engineering contains selected papers submitted to and presented at the 13th "Transport Systems. Theory and Practice" Scientific and Technical Conference organised by the Department of Transport Systems and Traffic Engineering at the Faculty of Transport of the Silesian University of Technology. The conference was held on 19-21 September 2016 in Katowice (Poland). More details at www.TSTP.polsl.pl.
I Quantitative and Qualitative Determinants of the Development of Transport Systems -- II Optimisation of Transport Systems.-III Safety Analysis in Advanced Transport Systems -- IV Advanced Systems of Traffic Engineering and Travel Models.
Keywords: Computational intelligence; Transportation engineering; Traffic engineering; Artificial intelligence; Computational Intelligence; Transportation Technology and Traffic Engineering; Artificial Intelligence